Preparing for the Next Cyber Revolution How Our World Will Be Radically Transformed-Again! - Pelton, Joseph N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Prepare yourselves for the coming Cyber Revolution! Over time, humankind has transformed from hunter-gatherer to farmer, from farmer to industrial worker, and from industrial worker to service provider. Now, we are on the cusp of a fourth transformative wave, spurred by climate change, exponential population growth, and our ever-increasing reliance on technology. This Copernicus book follows the stream of changes we will likely experience over the next few decades. These will involve the design and planning of smart cities and vital new mega-cities, as well as the use of sophisticated artificial intelligence and knowledge systems in our professional and everyday lives. The book shows how the nature of work, economics, taxation, social intercourse, and a slew of other global human endeavors will almost certainly undergo fundamental shifts during this time. Despite the many crises the world is gearing up to face, this book is not all doom and gloom - it is a call to action, a guide to how we might harness novel technologies in space and cyberspace to address our most urgent needs.
Acknowledgements -- About the Author -- Chapter 1: What Is the Cyber Revolution? -- Chapter 2: We Need Better Planet Management Skills -- Chapter 3: The Prime Drivers of Change -- Chapter 4: Smart Cities, Megacities and Meta-Cities -- Chapter 5: Climate Change and Sustainable Development -- Chapter 6: Life in a Cybernetic World -- Chapter 7: Where Is Technology Leading Us: The Good, the Bad, and the Ugly -- Chapter 8: Healthcare and Educational Systems in the Age of the Cyber Revolution -- Chapter 9: Political and Economic Reform in the Fourth Wave -- Chapter 10: Brave New World -- Appendix A: the U. N. Sustainable Development Goals -- Glossary -- Appendix B: Key Issues of the European General Data Protection Regulation -- Appendix C: U. S. Consumer Privacy Bill of Rights -- Index.
Keywords: Engineering; Artificial intelligence; Sociology, Urban; Control engineering; Robotics; Automation; Climatology; Computer engineering; Computer networks .; Technology and Engineering; Artificial Intelligence; Urban Sociology; Control, Robotics, Automation; Climate Sciences; Computer Engineering and Networks